2012
DOI: 10.1177/1040638712441605
|View full text |Cite
|
Sign up to set email alerts
|

A rapid mismatch polymerase chain reaction assay to detect carriers of complex vertebral malformation in Holstein cattle

Abstract: Abstract. Three Holstein sires were identified as complex vertebral malformation (CVM) carriers using the polymerase chain reaction-primer introduced restriction analysis (PCR-PIRA) method. Using the carriers as positive controls, the PCR mismatch amplification mutation assay (MAMA PCR) method was developed and validated by sequence analysis. With MAMA PCR, 154 Chinese Holstein sires were tested for CVM, among which 24 were confirmed to be CVM carriers. With DNA isolated from hair follicles, 10 daughters of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Twenty-six and thirty-four CVM carriers were identified, corresponding to the heterozygote carrier frequency of 21.6% (26) and 34% ( 14) respectively in Iran, and no mutant homozygote was found. In China, it has been reported that the frequency of the carrier animals are 10.48% (33), 2.92 % (29) and 15.58% (30) in Holstein cattle. In our country, Kulaklı and Akyüz (17) did not find carriers of CVM.…”
Section: Holştayn ıRkı Sığırlarda Sığır Lökosit Bağlanma Yetmezliği Faktör XI Eksikliği Ve Kompleks Vertebral Malformasyon Hastalıkları Gmentioning
confidence: 99%
“…Twenty-six and thirty-four CVM carriers were identified, corresponding to the heterozygote carrier frequency of 21.6% (26) and 34% ( 14) respectively in Iran, and no mutant homozygote was found. In China, it has been reported that the frequency of the carrier animals are 10.48% (33), 2.92 % (29) and 15.58% (30) in Holstein cattle. In our country, Kulaklı and Akyüz (17) did not find carriers of CVM.…”
Section: Holştayn ıRkı Sığırlarda Sığır Lökosit Bağlanma Yetmezliği Faktör XI Eksikliği Ve Kompleks Vertebral Malformasyon Hastalıkları Gmentioning
confidence: 99%
“…The prevalence of CVM carriers in Thrace region of Turkey (3.2%) was lower than those for Holstein cattle reared in Japan (32.5% and 13.0%) [ 11 16 ], Denmark (31.0%) [ 24 ], Poland (24.8%) [ 20 ], Sweden (23.0%) [ 5 ], Germany (13.2%) [ 14 ], China (15.6%, 14.7%, 9.54%, and 7.7%) [ 7 23 26 27 ], and Slovakia (8.5%) [ 10 ], but it was higher than that in Iran [ 12 19 ] (0%). The instructions on procedures and principles associated with sperm imports to Turkey was revised for CVM-carrier bull sperm by the Ministry of Food Agriculture and Livestock in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, sporadic CVM cases were reported from the USA [ 9 ] and the United Kingdom [ 18 ]. Subsequently, studies to identify CVM carriers were conducted in Japan [ 11 16 ], Germany [ 14 ], Sweden [ 5 ], Czech Republic [ 8 ], Poland [ 20 ], Turkey [ 15 ], China [ 7 23 26 27 ], Slovakia [ 10 ], and Iran [ 12 19 ]. Allele-specific polymerase chain reaction (AS-PCR) [ 11 ], created restriction-site PCR (CRS-PCR) [ 25 ], PCR with primer-introduced restriction analysis (PCR-PIRA) [ 13 ], and DNA sequencing [ 15 ] methods have been reported as capable of detecting the mutant allele that causes the CVM disorder.…”
Section: Introductionmentioning
confidence: 99%